Exploring the protective capabilities developed by hospital nurses to deflect workplace violence: a qualitative study in Taiwan - Tsu-Chi Wang; Ting-Ya Kuo; Tao-Hsin Tung; Peter Y. Chen; Fu-Li Chen (BMC, 2024)
Abstract Background Workplace violence is a serious safety hazard in the healthcare sector and has attracted much attention worldwide, especially for nursing staff. Equipping nursing personnel with protective capabilities for workplace violence can reduce the risk they face in work settings. This study explored scenarios of common violent patient-nurse conflicts in the workplace of hospital nursing staff and their capabilities for de-escalating such conflicts. Methods We used a qualitative content analysis for this study. Qualitative interviews were conducted with 21 nurses in two teaching hospitals in New Taipei City, Taiwan, until data saturation was reached. The data were transcribed, encoded, and analyzed and similar concepts were grouped under the same category. Results Four categories of workplace violence scenarios common to hospital nursing staff were identified: unreasonable requests, caring for high-risk patients, long waiting times for medical consultation, and close contact when caring for patients. Two protective capabilities were recognized: communication and interpersonal capabilities and problem-solving skills. Each scenario may require a different combination of abilities. Conclusion Our findings suggest that a violence-prevention training program could be designed for various workplace violence scenarios to enhance nurses' abilities to de-escalate workplace violence in hospitals.